Recovery The Glory of Asa And Ede of Yoruba Language: Library as A Tool - Olayinka Omolayo Aturamu; Akole Olatubosun Busuyi (Educare: Journal Educational and Multimedia, 2024)
This article explores the current state of asa and ede in the Yoruba language with a view of employing the library as a tool for the recovery of the lost glory. Some of the undermining factors working against the Yoruba language that were established in this study are globalization and westernization, urbanisation and migration, educational policies, socioeconomic pressures and the impact of colonial legacy. However, ‘libraries’ employed in a wide range of contexts, from digital libraries to physical public libraries play crucial roles in cultural heritage preservation through collection and preservation, digitization initiatives archiving, oral traditions education and literacy Programmes, community engagement and outreach research and scholarly support and leveraging technology. Some successful organizational, institutional and individual cultural preservation programmes were equally highlighted.